Formal semantics and analysis of tokenomics properties - Letychevskyi, O.O.; Peschanenko, V.S.; Poltorackiy, M.Yu.; Tarasich, Yu.H.; Vinnyk, M.O. (Проблеми програмування, 2022)
Today we are witnessing the rapid development of products and services based on blockchain technology. Cryptocurrencies and tokens are becoming an integral part of a person’s daily life. One of the main and, at the same time, the most difficult task for each project is the creation of a self-governing token economy. The violation of properties, such as equilibrium and decentralization, can result in the failure of a project and financial losses. Using the math and formal methods is a simple and efficient way to create self-sustainable token economies right at the stage of MVP development. Despite the rapid development of tokenomics, its popularity, and the rapid pace of implementing blockchain technology in various business areas, only a small number of works have examined formal models of tokenomics. In this study, we present an algebraic approach to analyzing the properties of tokenomics. The algebraic modeling approach is implemented within the framework of the Insertion Modeling System (IMS) that was developed at the Glushkov Institute of Cybernetics of the National Academy of Sciences of Ukraine under the guidance of an Academician of the National Academy of Sciences of Ukraine, Professor A.A. Letichevsky. The algebraic modeling methods prove the properties of safety and liveness. Insertion modeling is an approach for modeling complex distributed systems, which is based on the theory of interaction between agents and environments. The modeling algorithm is based on the historical data of exchange trading and the liquidity of tokens - which allows us to make accurate predictions and show possible outcomes. The interaction of tokenomics agents and their behavior, represented by the equations of behavioral algebra, is considered. The use of the algebraic approach to tokenomics development for the Internet of Things is considered, and the formal representations and methods of property analysis are presented. The obtained results allow us to discuss the possibility of using formal methods in the study of tokenomics.